Better Evidence and UpToDate Training Module 4: Using Your Institutional Account - Kabale University Library (Kabale University, 2023)
The module briefly explains UpTodate Global Health Topics, Institutional Subscription, Continuing Medical Education (CME) Credit through UpToDate and Becoming an UpToDate Certified Trainer